2021
DOI: 10.1111/aos.14955
|View full text |Cite
|
Sign up to set email alerts
|

The association of neutrophil–lymphocyte ratio and platelet–lymphocyte ratio with retinal vein occlusion: a systematic review and meta‐analysis

Abstract: The neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR) are emerging haematological inflammatory biomarkers. However, their significance in retinal vein occlusion (RVO) and its subtypes, branch and central RVO (BRVO and CRVO, respectively), is uncertain. This systematic review and meta‐analysis aimed to clarify the association of NLR and PLR with RVO. We searched MEDLINE (Ovid), EMBASE (Ovid) and the Cochrane Library for studies investigating the association of NLR and PLR with RVO from incep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Previous studies have demonstrated that the systemic infection response plays a critical role in the symptom response [ 8 , 9 ]. Many clinical inflammation markers, such as neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR), can be easily measured via relatively inexpensive tests and with accurately reliable clinical results in several types of cancers and other diseases [ 10 17 ]. There have also been articles reporting that the predicting value of NLR and PLR in not only viable foe surgical treatment of early stage NSCLC but also in chemo-radiotherapy and immunotherapy of advanced NSCLC [ 13 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the systemic infection response plays a critical role in the symptom response [ 8 , 9 ]. Many clinical inflammation markers, such as neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR), can be easily measured via relatively inexpensive tests and with accurately reliable clinical results in several types of cancers and other diseases [ 10 17 ]. There have also been articles reporting that the predicting value of NLR and PLR in not only viable foe surgical treatment of early stage NSCLC but also in chemo-radiotherapy and immunotherapy of advanced NSCLC [ 13 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently discovered different possible biomarkers for predicting RAO or RVO from normal blood analysis. The connection between NLR and RVO was revealed ( Table 1 ) [ 19 23 ]. Furthermore, the monocyte to high-density lipoprotein ratio (MHR), rather than PLR, may be a useful predictor for the development of RAO [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior researches have looked at the effects of NLR and PLR on predicting RAO or RVO [19][20][21][22][23][24][25][26]43,49,50]. In some investigations, NLR has already been shown to be a unique marker for predicting RAO [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently discovered different possible biomarkers for predicting RAO or RVO from normal blood analysis. The connection between NLR and RVO was revealed (Table 1) [19][20][21][22][23]. Furthermore, the monocyte to high-density lipoprotein ratio (MHR), rather than PLR, may be a useful predictor for the development of RAO [24][25][26].…”
Section: Introductionmentioning
confidence: 99%